2015
DOI: 10.1074/jbc.m115.677401
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of Hyperglycemic Dividing Mesangial Cells to Heparin Are Mediated by the Non-reducing Terminal Trisaccharide

Abstract: Background: Heparin prevents intracellular hyaluronan synthesis and subsequent autophagy in hyperglycemic dividing mesangial cells. Results: The non-reducing terminal trisaccharide of heparin is sufficient for this response. Conclusion: This heparin trisaccharide motif is exposed by the mammalian heparanase and is recognized by a receptor on dividing cells. Significance: The trisaccharide does not have the anti-coagulant properties of heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…We have shown that heparin interferes with intracellular HA synthesis, ER stress and the induced inflammatory responses in hyperglycemic stressed cells [8,13,29]. Further, the non-reducing terminal trisaccharide of heparin, Hep-Tri, is sufficient to reverse the hyperglycemic stress responses [14]. This is very significant because Hep-Tri lacks the deleterious side effects of heparin.…”
Section: Future Studies and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that heparin interferes with intracellular HA synthesis, ER stress and the induced inflammatory responses in hyperglycemic stressed cells [8,13,29]. Further, the non-reducing terminal trisaccharide of heparin, Hep-Tri, is sufficient to reverse the hyperglycemic stress responses [14]. This is very significant because Hep-Tri lacks the deleterious side effects of heparin.…”
Section: Future Studies and Conclusionmentioning
confidence: 99%
“…Hyperglycemic: Cells that divide in hyperglycemic glucose levels activate HASs in intracellular membranes entering S phase. This inserts the large, polyanionic HA intracellularly into ER, Golgi and transport vesicles, which induces ER stress and autophagy responses and extrusion of an extracellular monocyte-adhesive HA matrix after division [8,14]. Heparin/Hep-Tri: Low concentrations (Kd ~20 nM) of heparin and of Hep-Tri prevents the intracellular HA synthesis and reprograms the cells to synthesize a monocyte-adhesive extracellular HA matrix after division [8,14].…”
Section: Hyperglycemia and Heparinmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM5B modulates the expression of tumor suppressors and oncogenes by regulating the methylation levels of H3K4 in cancer cells [28,31]. A study by Wang et al (2015) used high risk B-ALL cells to investigate regulation of this important global epigenetic regulator, KDM5B [32]. Increased expression of KDM5B was observed in B-ALL cells compared to normal bone marrow.…”
Section: Lysine-specific Demethylase 5b (Kdm5b)mentioning
confidence: 99%
“…Subsequent studies showed that low concentrations of heparin (ϳ0.3 g/ml) were sufficient 1) to prevent the intracellular hyaluronan synthesis and autophagy and 2) to re-program the cells to finish cell division and then synthesize the extensive extracellular hyaluronan matrix that is monocyte-adhesive (47). Furthermore, the nonreducing trisaccharide of heparin (Hep-Tri) (K d ϳ20 nM) is sufficient (48). These results provide evidence that hyperglycemic dividing cells have a cell-surface receptor that interacts with the Hep-Tri to re-program the cells to block intracellular hyaluronan synthesis.…”
Section: Abnormal Intracellular Hyaluronan Synthesis In Hyperglycemic Dividing Cells (2004 -2014)mentioning
confidence: 99%